Delivery of dietary triglycerides to Caenorhabditis elegans using lipid nanoparticles: Nanoemulsion-based delivery systems. (1st July 2016) - Colmenares, Daniel; Sun, Quancai; Shen, Peiyi; Yue, Yiren; McClements, D. Julian; Park, Yeonhwa
Highlights: A nanoemulsion-based method to deliver triglycerides to C. elegans was tested. C. elegans ingested triglyceride nanoparticles with particle size 40–500 nm. Ingestion of CLA nanoparticles by C. elegans significantly reduced fat accumulation. Nanoparticles may be applied to evaluate hydrophobic compounds in C. elegans . Abstract: The nematode Caenorhabditis elegans is a powerful tool for studying food bioactives on specific biochemical pathways. However, many food bioactives are highly hydrophobic with extremely low water-solubilities, thereby making them difficult to study using C. elegans . The purpose of this study was to develop nanoemulsion-based systems to deliver hydrophobic molecules in a form that could be ingested by C. elegans . Optical microscopy showed that oil-in-water nanoemulsions with a range of particle diameters (40–500 nm) could be ingested by C. elegans . The amount of lipid ingested depended on the size and concentration of the nanoparticles. Fatty acid analysis showed incorporation of conjugated linoleic acid and there was a significant reduction in the fat levels of C. elegans when they were incubated with nanoemulsions containing conjugated linoleic acid, which suggested that this hydrophobic lipid was successfully delivered to the nematodes. The incorporation of hydrophobic molecules into nanoemulsion based-delivery systems may therefore enable their activities to be studied using C. elegans .